2013
DOI: 10.6061/clinics/2013(11)08
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme gene 2350 G/A polymorphism and susceptibility to atrial fibrillation in Han Chinese patients with essential hypertension

Abstract: OBJECTIVE:The angiotensin-converting enzyme gene is one of the most studied candidate genes related to atrial fibrillation. Among the polymorphisms of the angiotensin-converting enzyme gene, the 2350 G/A polymorphism (rs4343) is known to have the most significant effects on the plasma angiotensin-converting enzyme concentration. The aim of the present study was to investigate the association of the angiotensin-converting enzyme 2350 G/A polymorphism with atrial fibrillation in Han Chinese patients with essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 36 publications
(50 reference statements)
0
11
0
1
Order By: Relevance
“…Current smoking, hypertension, diabetes mellitus, and atrial fibrillation were defined according to past literature reports [13][14][15]. Details of medical history, as well as physical and laboratory examination, were obtained from all patients before performing the coronary angiography.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Current smoking, hypertension, diabetes mellitus, and atrial fibrillation were defined according to past literature reports [13][14][15]. Details of medical history, as well as physical and laboratory examination, were obtained from all patients before performing the coronary angiography.…”
Section: Methodsmentioning
confidence: 99%
“…The measurement of total cholesterol, high-density lipoprotein-cholesterol, lowdensity lipoprotein-cholesterol, triglycerides, and hs-CRP was performed as described previously [14][15][16]. Blood samples for high-sensitivity C-reactive protein (hs-CRP) and YKL-40 were drawn from the radial sheath before selective coronary angiography was performed.…”
Section: Biochemical Measurementsmentioning
confidence: 99%
“…Implicated genes include those encoding connexin 40, GJA5 [7, 6769], the transcription factor gene NKX2.5 [70, 71], and the LMNA gene[72]. Genes involved in the renin-angiotensin-aldosterone pathway, including the angiotensin converting enzyme, angiotensin gene promoter and angiotensinogen[7376], have also been associated with AF.…”
Section: Polygenic Non-familial Common Afmentioning
confidence: 99%
“…Some studies of patients with essential hypertension have identified RAAS gene variants that are related to increased risk of AF [73, 76, 137]. Polymorphisms in this system have also been linked to stroke.…”
Section: Risk Factors For Af: Hypertension Obesity and Common Genetimentioning
confidence: 99%
“…During last 20 years, numerous AF associated mutations, candidate genes, and risk loci have been identified [1419]; however, much of the heritability of AF remains unexplained [20]. Recently, Sinner et al [21] identified that 6 polymorphisms in 5 novel loci (NEURL rs12415501 and rs6584555, CAND2 rs4642101, GJA1 rs13216675, TBX5 rs10507248, and CUX2 rs6490029) were associated with atrial fibrillation susceptibility using a combination of genotyping, eQTL mapping, and functional validation.…”
Section: Introductionmentioning
confidence: 99%